2014
DOI: 10.1111/meta.12107
|View full text |Cite
|
Sign up to set email alerts
|

You Make Your Own Luck

Abstract: This essay takes up two questions. First, what does it mean to say that someone creates her own luck? At least colloquially speaking, luck is conceived as something out of an agent's control. So how could an agent increase or decrease the likelihood that she'll be lucky? Building on some recent work on the metaphysics of luck, the essay argues that there is a sense in which agents can create their own luck because people with more skill tend to have more opportunities to benefit from luck. Second, what implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…68-69). 6 In this manner, it is suggested that developing certain epistemic skills increases the likelihood of becoming scientifically lucky, such as training certain virtues increases the likelihood of becoming morally lucky (Copeland 2017;McKinnon 2014). In so far as it is up to the agent to deliberately train such skills or accept certain risks when driving negligently, these freely adopted volitions constitute the basis of someone's moral standing (Concepcion 2002, p. 459).…”
Section: Moral Luck and Common Objectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…68-69). 6 In this manner, it is suggested that developing certain epistemic skills increases the likelihood of becoming scientifically lucky, such as training certain virtues increases the likelihood of becoming morally lucky (Copeland 2017;McKinnon 2014). In so far as it is up to the agent to deliberately train such skills or accept certain risks when driving negligently, these freely adopted volitions constitute the basis of someone's moral standing (Concepcion 2002, p. 459).…”
Section: Moral Luck and Common Objectionsmentioning
confidence: 99%
“…An inherited scientific curiosity does not help one telling apart a dirty petri dish from one that contains an important antibacterial substance. These skills have to be learned and continuously trained, which requires diligence and effort (Copeland 2017;McKinnon 2014).…”
Section: Different Types Of Luck and A Defence Of The Control Principlementioning
confidence: 99%
“…In the ensuing decade, him and many others have proposed more or less friendly amendments, but the general model remains the same (see e.g. Turri 2011; McKinnon 2013; Littlejohn 2014; McKinnon 2014; Carter, Jarvis, and Rubin 2015; Sosa 2015; Turri 2016). According to Sosa, achievements have what he calls a ‘AAA structure’.…”
Section: Ability-based Accountsmentioning
confidence: 99%
“…For a contemporary view on the metaphysics of luck, seeMcKinnon (2013b) andMcKinnon (2014) 7. CompareWilliamson (2000), DeRose(2002), and others.10.1057/9781137521729 -The Norms of Assertion, Rachel McKinnonCopyright material from www.palgraveconnect.com -licensed to University of Alberta -PalgraveConnect -2015-08-03…”
mentioning
confidence: 99%